Analysis Fenomena Peer Group Bullying dengan Psikologi Belajar Mahasiswa di Perguruan Tinggi - Asa Amelia Habni; Mia Agustinam; Rafeyfa Mahdiyasila; Revalinda Putri Fauziah; Ulfa Ulil Hidayah; Joko Tri Nugraha (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This research is motivated by the importance of peer interaction in the dynamics of student life in an academic environment. Social interactions between students not only serve as a means of providing emotional support but can also have negative impacts, manifesting in the form of bullying. The phenomenon of bullying in higher education has the potential to reduce psychological well-being and simultaneously hinder the smooth learning process. Based on these conditions, this study aims to examine in-depth the relationship and influence of peer group bullying on students' learning psychology. This study used a quantitative approach with a correlational design. Data collection was conducted through the distribution of an online Likert-scale questionnaire to 81 respondents, students of the Public Administration Study Program. The research instrument was designed to measure aspects of bullying, including physical, verbal, social, and mental dimensions, as well as aspects of learning psychology, including concentration, motivation, self-confidence, and mental readiness. Based on the data analysis, a relationship was found between peer group bullying and students' learning psychology, but the strength of this relationship was categorized as weak. Furthermore, statistical tests indicated that bullying did not have a significant direct impact on the learning psychology of the respondents in this study. These findings indicate that student learning psychology is a complex variable, not solely determined by peer interactions but also influenced by other internal and external factors, such as self-motivation, family support, and the overall academic climate.